Potential Vocabulary Growth in EMI Programs: The Cases of Accounting and Civil Engineering in Taiwanese EFL context - Hsu, Wenhua (JET (Journal of English Teaching), 2021)
English-medium instruction (EMI) has become a nationwide trend in Taiwan’s higher education institutions. Behind this rapid growth is the widespread belief that EMI provides English immersion, which facilitates incidental learning of the target language. However, not all EMI programs in EFL contexts provide the same immersion as those in the Anglosphere. English-medium university textbooks were therefore targeted as a research focus in that they offer non-English subject majors a sustainable channel for exposure to English in the EFL context. The researcher compiled two 4-million-token accounting and civil engineering textbook corpora and measured the vocabulary levels and amounts along the BNC/COCA word-frequency scale. Results show that accounting textbooks reached the 5th 1000-word-family level at 98% text coverage while civil engineering textbooks stretched to the 9th–10th 1000 level. Twelve repetitions were used as a benchmark for incidental learning. Only 1,479 word families beyond the first 3000 occurred 12+ times in the accounting corpus versus 3,397 word families in the civil engineering corpus. For EMI practitioners who are concerned with their students’ vocabulary development, the results may serve as a reference for future investigations into other disciplines.